Opportunities For Integration And Joint Development Between Entrepreneurship - Adane Abdesselam, Sidali; Radjef, Nacera (جامعة الوادي University of Eloued, 2025)
This paper examines a partnership and cooperation agreement between the Algerian Foundation for Youth Support and Entrepreneurship Development and the Trades and Traditional Industries Chamber of Tissemsilt. The study aims to understand the objectives, mechanisms and results of this Convention and how it affects and supports the entrepreneurship of young professionals in the areas of crafts and traditional industries; The study seeks to assess the Convention's impact on local economic development by analyzing available information, exploring its effectiveness in achieving its objectives and stimulating sustainable development in the relevant sectors. The study revealed that the integration of entrepreneurship and traditional industries in Algeria supports economic growth and sustainable development, as entrepreneurship promotes industrial progress through technical and technological modernization and supports production and marketing, and contributes traditional industries by providing skilled labor and creative ideas.
Opportunities for Integration and Joint Development between Entrepreneurship and Traditional Industry: A Case Study
مقال
Keywords: Entrepreneurship; Entrepreneurial; Accompaniment; Development